Competency Analysis Customer Service Communication In Keeping Customer Loyalty - Arif Gunawan; Yanto Yanto; Fera Indasari (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
In the development of information and communication PT Telkom always improves service to customers, therefore Customer Service always gives the best to maintain customer loyalty therefore this research, discussing the competence of customer service communication in maintaining customer loyalty in PT products. Telkom Indonesia branch of Bengkulu City.  The purpose of this research is to know and analyze the competence of Customer Service communication in maintaining customer loyalty in achieving the results. The method used in this study is descriptive skin to give a clear picture of the research problem. aspects guided by murphy and hildebrandt theory (1991) namely in communication there are seven aspects including Completeness, concisenes, Concretness, consideration, clarity, Courtesy, and corretness in this study the author only took four aspects including Completeness, Concisiness, Concretness, and Courtesy. The reason is because in the four aspects it can already represent the whole. The results of research in the field showed that completeness or completeness of information provided by customer service has been implemented well, customer service leaders have also conducted monitoring of customer service in providing complete information in the concisiness admin customer service has been well directed to provide clear information to customers on aspects of customer service admin concretness has also carried out the delivery of information in accordance with procedures so that customers can receive information provided by customer service. Courtesy has been implemented well as conveyed by the head of customer service that serving customers must be friendly, polite and polite and manners so that customers feel comfortable when doing activities related to PT Telkom products.